Sarcomatoid carcinoma of the gallbladder: A rare and aggressive form of gallbladder cancer - Faten Limaiem; Rached Bayar; Sahir Omrani (Clinical Case Reports, 2023)
Abstract Sarcomatoid carcinoma is a rare type of gallbladder cancer with less than 100 cases reported in the literature. Preoperative diagnosis is difficult due to nonspecific clinical and radiological findings. Its prognosis is poor due to rapid progression and a high short‐term recurrence rate. The definitive diagnosis relies on histopathological examination.